1987
DOI: 10.1080/00288330.1987.9516258
|View full text |Cite
|
Sign up to set email alerts
|

Dinoflagellate resting cysts isolated from sediments in Marlborough Sounds, New Zealand

Abstract: Seventeen species of dinoflagellate resting cysts have been recorded for the first time in New Zealand. Isolated from sediments at 93 locations in the Marlborough Sounds, these were Gonyaulax spinifera, G. grindleyi, G. polyedra, G. digitalis, Gonyaulax sp., Protoperidinium subinerme, P. pentagonum, P. conicum, P. oblongum, P. leonis, P. cf punctulatum, P. cf. conicoides, Peridinium stellatum, Peridinium sp., Scrippsiella trochoidea, Polykrikos schwartzii, and Diplopsalis sp. here possible their identities wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 20 publications
(16 reference statements)
2
15
0
Order By: Relevance
“…This cyst, which can withstand palynolog~cal treatment (Anderson et al 1988, Nordberg & Bergsten 1988, has never been observed in prehistoric Australian sediments (McMinn 1989(McMinn , 1992a. It was also absent in a survey of Recent sediments from the entire east coast of mainland Australia (McMinn 1990(McMinn , 1991 and from New Zealand (Baldwin 1987). Recently, however, G. catenatum cysts have been detected in sediments, from Warrnambool and Lorne, Victoria (Sonneman & Hill 1997), and from Port L~ncoln, South Australia (Hallegraef unpubl.…”
Section: Introductionmentioning
confidence: 99%
“…This cyst, which can withstand palynolog~cal treatment (Anderson et al 1988, Nordberg & Bergsten 1988, has never been observed in prehistoric Australian sediments (McMinn 1989(McMinn , 1992a. It was also absent in a survey of Recent sediments from the entire east coast of mainland Australia (McMinn 1990(McMinn , 1991 and from New Zealand (Baldwin 1987). Recently, however, G. catenatum cysts have been detected in sediments, from Warrnambool and Lorne, Victoria (Sonneman & Hill 1997), and from Port L~ncoln, South Australia (Hallegraef unpubl.…”
Section: Introductionmentioning
confidence: 99%
“…There is no historic evidence of PSP in New Zealand (Baldwin 1987;Mackenzie 1990); however, Cembella et al (1987) have confirmed the presence of paralytic shellfish toxins (GTX i+4 , GTX 2+ 3 and STX) in a dinoflagellate isolate from Whangarei. Further, there is concern about possible introductions via cysts in the ballast water of visiting ships (Hallegraeff & Bolch 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Photomicrographs of cysts were taken with a Optronix DEI-750 CE camera system using Image-Pro software. Cyst identification was based upon morphological criteria described in the literature (Fukuyo 1982, Dale 1983, Baldwin 1987. The correspondences between ship/tank variables and dinoflagellate/ cyst presence-absence and absolute/relative abundances within assemblages initially were determined using Pearson product moment correlation coefficients (SYSTAT 10 2000).…”
Section: Methodsmentioning
confidence: 99%